2015
DOI: 10.1111/jen.12229
|View full text |Cite
|
Sign up to set email alerts
|

Non‐target effects of insecticides, entomopathogenic fungi and nematodes applied against western corn rootworm larvae in maize

Abstract: Field studies were conducted in southern Hungary over two field seasons to assess potential non-target effects of entomopathogenic nematodes (Heterorhabditis bacteriophora), entomopathogenic fungi (Metarhizium anisopliae), clothianidin-coated seeds and tefluthrin granules applied into the soil against larvae of the chrysomelid Diabrotica virgifera virgifera, one of the major North American and European maize pests. From field gauze cages set up over groups of maize plants, 1944 specimens of non-target ground-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Applied H. bacteriophora nematodes were detected almost four months after application in sandy loam soil at site 2 and almost five months after application in silty loam soil at site 1, which supports previous research [32,34,56]. These studies showed that the applied nematodes were able to survive in the soil for approximately one month without their host, which hatches 2-4 weeks after maize sowing and EPN application.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Applied H. bacteriophora nematodes were detected almost four months after application in sandy loam soil at site 2 and almost five months after application in silty loam soil at site 1, which supports previous research [32,34,56]. These studies showed that the applied nematodes were able to survive in the soil for approximately one month without their host, which hatches 2-4 weeks after maize sowing and EPN application.…”
Section: Discussionsupporting
confidence: 87%
“…Field efficacy assessment of EPF, EPN, and insecticides revealed that EPF application shows lower efficacy than EPN or insecticides [28]. An evaluation of the potential non-target effects of these biological and chemical control agents was investigated by Babendreier et al (2015) [32]. However, a more recent field study showed that a combination of entomopathogens with chemical insecticides performed better than either product alone [33].…”
Section: Introductionmentioning
confidence: 99%
“…Feeding by adults can cause the damage on leaves, flowers, pollen and silk by characteristic injuries (Trusca, 2013). in the nematode treatment, 3.15 in the fungus treatment, 1.89 in the tefluthrin treatment and 1.43 specimens in the clothianidin treatment (Babendreier et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Third, in comparison to chemical pesticides, the multiple mode of action of EPF lessens the possibility of resistance development in insects [83]. Fourth, EPF pathogenicity is specific to insects, avoiding unexpected deleterious effects on non-target plant-beneficial organisms [84,85]. In this context, the great diversity of EPF strains allows selecting the most pathogenic ones, depending on the type of root pest and environmental factors [86].…”
Section: Fungimentioning
confidence: 99%